Determination of layer morphology of rough layers in organic light emitting diodes by X‐ray reflectivity. Issue 4 (20th November 2022) - Sachs, Ian; Fuhrmann, Marc; Deferme, Wim; Möbius, Hildegard
Abstract: X‐ray reflectivity (XRR) has been proven to be a useful tool to investigate thin layers as well as buried interfaces in stacks built of very thin layers. Nevertheless, x‐ray reflectivity measurements are limited by the roughness of the layers and interfaces as the roughness destroys the interference structure, the so‐called Kiessig fringes. As investigations of thin layers in organic light emitting devices (OLEDs) are still subject of research and development, the focus of this paper is the investigation of a layer of indium tin oxide (ITO) which serves as transparent anode material in OLEDs. Due to the fabrication process, ITO shows rough surface structures, so‐called spikes, hindering the determination of the ITO layer thickness and roughness in XRR measurements. In this paper, it is theoretically and experimentally proven that a smoothing layer on the ITO enables the determination of the buried ITO layer thickness and roughness as well as the density of the spikes. Furthermore, a sputtered aluminum layer (e.g. cathode material) showing spikes in atomic force microscopy covered with a smoothing layer reveals Kiessig fringes allowing the determination of the density of buried spikes. In general, it is shown that a smoothing layer on a rough surface enhances the sensitivity of x‐ray reflectivity measurements. Abstract : Enhancing the sensitivity of x‐ray reflectivity measurements of rough layers with buried spikes using a smoothing layer. The smoothing layer reveals Kiessing fringes allowing the determination of the density of buried spikes and other layer properties